Study of electric power quality indicators by simulating a hybrid generation system - Frank Grau Merconchini; Luis Vázquez Seisdedos; Janette Cervantes Oliva; José Ricardo Núñez Alvarez; David Checa-Cervantes (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Currently, as part of the distributed generation paradigm, photovoltaic energy has a growing development. The diversity of the loads, their nonlinearity, and the penetration of the renewable energy sources (RES) cause a worsening of the energy quality indicators. The main quality indicators that affect hybrid photovoltaic systems are voltage and current harmonic distortion, voltage deviation, and voltage and current asymmetry in the system. The construction of physical and mathematical models in software applications, such as MATLAB, Simulink, and Simscape, makes it possible to simulate the operating conditions of these systems and determine the values of the indicators that account for the quality of the electric power supplied. In this work, the modeling and simulation of a photovoltaic system connected to the network that feeds a mixed industrial area are carried out to determine the indicators of energy quality.